A case of adenomyosis with leiomyoma that was effectively treated with relugolix and kamishoyosan add-on therapy - Yukifumi Sasamori; Kohei Takehara; Tsuyoshi Terashima; Takako Onodera; Keita Yatsuki; Ippei Nakagawa; Yuko Takahashi; Haruka Nishida; Takayuki Ichinose; Haruko Hiraike; Kazunori Nagasaka (BMC, 2021)
Abstract Background Recently, relugolix, an oral gonadotropin-releasing hormone receptor antagonist, has been considered an effective therapy for leiomyoma based on a phase 3 study in Japanese women. Leiomyoma combined with severe adenomyosis occasionally occurs in perimenopausal women; however, little information on the effectiveness of relugolix against severe adenomyosis exists. Case presentation A 49-year-old woman was referred to our hospital with acute lower abdominal pain and abnormal uterine bleeding. Magnetic resonance imaging revealed multiple leiomyomas with diffuse adenomyosis. Left hydrosalpinx was also observed. The patient refused surgical treatment and preferred oral relugolix. Since she experienced a hot flush and headache induced by relugolix, a traditional Japanese Kampo, kamishoyosan, was added to improve the side effects of relugolix. The patient was asymptomatic at the time of this report and experienced a significant shrinkage in uterine volume. Ultimately, she avoided hysterectomy as desired. Conclusions To our knowledge, this is the first report of co-occurring adenomyosis and leiomyoma, which was effectively treated with relugolix. Although the management of adverse side effects, including hot flush and headache by relugolix, has recently attracted attention and controversy, relugolix add-on therapy with kamishoyosan may help treat menopausal symptoms.